Hydrochemical evaluation of changing glacier meltwater contribution to stream discharge: Callejon de Huaylas, Peru - Mark, Bryan G. (2005)
Original abstract: Discharge measurements, precipitation observations and hydrochemical samples from catchments of the Callejon de Huaylas watershed draining the Cordillera Blanca to the Rio Santa, Peru, facilitate estimating the glacier meltwater contribution to streamflow over different spatial scales using water balance and end-member mixing computations. A monthly water balance of the Yanamarey Glacier catchment shows elevated annual discharge over December 2001–July 2004 compared to 1998–1999, with net glacier mass loss in all months. Glacial melt now accounts for an estimated 58% of annual mean discharge, 23% greater than 1998–1999. At Lake Querococha, below Yanamarey (3.4% glacierized), a hydrochemical end-member mixing model estimates that 50% of the streamflow is derived from the glacier catchment. Average concentrations from the Rio Santa leaving the Callejon de Huaylas (8% glacierized) are modelled as a mixture with 66% deriving from glacierized tributaries of the Cordillera Blanca as opposed to the non-glacierized Cordillera Negra end member.